Analisis Efektivitas Pengawasan Pergerakan Pesawat Udara Oleh Apron Movement Control di Apron Area Bandar Udara Internasional Zainudin Abdul Madjid Lombok - Fandi, Moh Razif; Kifni Yudianto (Lembaga Pengembangan Kinerja Dosen, 2024)
The increase in the number of users of air transportation modes that occurred in the last year period was 32.69 percent or 10.7 million people, causing a density in the number of flights and an increase in the fleet of aircraft in operation, therefore it is necessary to monitor aircraft movements, especially in the apron area. carried out properly to avoid accidents or things that could be dangerous for users or personnel on duty or related to air transportation. The purpose of this research is to determine the effectiveness of monitoring aircraft movements carried out by the Apron Movement Control unit in the apron area of Zainudin International Airport Abdul Madjid Lombok. The results of the research found that the process of monitoring aircraft movements in the apron area has been carried out following applicable regulations and rules, however, the equipment used to monitor aircraft movements in the form of CCTV requires repair and rejuvenation, related to the effectiveness of monitoring aircraft movements in the Apron Movement Control unit. Lombok's Zainudin Abdul Madjid International Airport has met five indicators that serve as benchmarks for work effectiveness.